Correlating Fibrinogen Consumption and Profiles of Inflammatory Molecules in Human Envenomation's by Bothrops atrox in the Brazilian Amazon - Wellmann, Irmgardt Alicia María; Ibiapina, Hiochelson Najibe Santos; Sachett, Jacqueline Almeida Gonçalves; Sartim, Marco Aurélio; Silva, Iran Mendonça; Oliveira, Sâmella Silva; Tarragô, Andréa Monteiro; Moura-da-Silva, Ana Maria; Lacerda, Marcus Vinícius Guimarães; Ferreira, Luiz Carlos de Lima; Malheiro, Adriana; Monteiro, Wuelton Marcelo; et al. (Frontiers in Immunology, 2020)
Snakebites are considered a major public health problem worldwide. In the Amazon region of Brazil, the snake Bothrops atrox (B. atrox) is responsible for 90% of the bites. These bites may cause local and systemic signs from acute inflammatory reaction and hemostatic changes, and present common hemorrhagic disorders. These alterations occur due the action of hemostatically active and immunogenic toxins which are capable of triggering a wide range of hemostatic and inflammatory events. However, the crosstalk between coagulation disorders and inflammatory reaction still has gaps in snakebites. Thus, the goal of this study was to describe the relationship between the consumption of fibrinogen and the profile of inflammatory molecules (cytokines and chemokines) in evenomations by B. atrox snakebites. A prospective study was carried out with individuals who had suffered B. atrox snakebites and presented different levels of fibrinogen consumption (normal fibrinogen [NF] and hypofibrinogenemia [HF]). Seventeen patients with NF and 55 patients with HF were eligible for the study, in addition to 50 healthy controls (CG). The molecules CXCL-8, CCL-5, CXCL-9, CCL-2, CXCL-10, IL-6, TNF, IL-2, IL-10, IFN-γ, IL-4 and IL-17A were quantified in plasma using the CBA technique at three different times (pre-antivenom therapy [T0], 24 hours [T1] and 48 hours [T2] after antivenom therapy). The profile of the circulating inflammatory response is different between the groups studied, with HF patients having higher concentrations of CCL-5 and lower IFN-γ. In addition, antivenom therapy seems to have a positive effect, leading to a profile of circulating inflammatory response similar in quantification of T1 and T2 on both groups. Furthermore, these results suggest that a number of interactions of CXCL-8, CXCL-9, CCL-2, IL-6 and IFN-γ in HF patients are directly affected by fibrinogen levels, which may be related to the inflammatory response and coagulation mutual relationship induced by B. atrox venom. The present study is the first report on inflammation-coagulation crosstalk involving snakebite patients and supports the better understanding of envenomation’s pathophysiology mechanisms and guides in the search for novel biomarkers and prospective therapies.